Improving access to multi-drug resistant tuberculosis diagnostic and health services for refugees and migrants - Zumla, Alimuddin; Abubakar, Ibrahim (BMC medicine, 2018)
By the end of 2017, an estimated 68.5 million people were displaced from their homes worldwide, of whom 25.4 million were refugees. The transmission and globalization of multi-drug resistant tuberculosis during refugee migration is a now priority issue in the public health agenda. Political and scientific commitment at the highest national and international levels will be critical to intensifying action in promoting improved health services for migrants and refugees.